'Roving Vultures': Television News and the Outbreak of the Troubles in Northern Ireland. Issue 4 (2nd October 2019) - Doherty, Martin
Abstract : In October 1968, an illegal civil rights march in Londonderry in Northern Ireland was broken up by the local police force, the Royal Ulster Constabulary. Hitherto, Northern Ireland, although a constituent part of the United Kingdom, was an unknown quantity for most British people, who knew or cared little about its endemic sectarian problems, and its one-sided and discriminatory system of government. Had the march taken place in 1958 rather than 1968, it very likely would be remained an item of local interest and controversy only. However, the presence in 1968 of three television crews, who recorded what transpired, meant that the problems of the province were cruelly exposed, leading to a spiral of violence known as 'the Troubles' which would cost the lives of some 3, 600 people in the succeeding decades.